Pengaruh Penguasaan Ilmu Tajwid Terhadap Keterampilan Membaca Al-Qur’an Santri Taman Pendidikan Al-Qur’an Nurul Hayat Kelurahan Tembilahan Barat - Zulkifli, Zulkifli; Zulkarnainsyah, Zulkarnainsyah; Muhammadiyah, Muhammadiyah (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2024)
This quantitative descriptive research is to determine the students' understanding and mastery of the science of recitation, whether it affects the Al-Qur'an reading skills of Nurul Hayat Al-Quran Educational Park students. In this research, data collection used test methods and documentation methods. The population included in this study were all students, totaling 42 students.